Effect of fermentation using Chrysonillia crassa and Monascus purpureus on nutritional quality, antioxidant, and antimicrobial activities of used rice as a poultry feed ingredient - Yudiarti, Turrini; Sugiharto, Sugiharto; Isroli, Isroli; Widiastuti, Endang; Wahyuni, Hanny Indrat; Sartono, Tri Agus (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study was aimed at evaluating the effect of fermentation using Chrysonillia crassa and Monascus purpureus on nutritional qualities, antioxidant, and antimicrobial activities of the used rice as a poultry feed ingredient. Materials and Methods: The used rice was soaked, steamed, and spread on a tray to cool. Suspension of M. purpureus or C. crassa was inoculated on the steamed used rice, and then mixed thoroughly. Afterward, the mixture was spread out on the tray, which was then covered with an aluminum foil. It was aerobically incubated for 7 and 4 days for the M. purpureus- and C. crassa-inoculated used rice, respectively. Subsequent to sun drying, the fermented used rice was grounded and analyzed. Results: Crude protein and ash contents were higher (p < 0.05) in the used rice fermented with C. crassa or M. purpureus than in the unfermented. Conversely, carbohydrate content was lower (p < 0.05) in the fermented compared with the unfermented. Gross energy and energy from fat were higher (p < 0.05) in the used rice fermented with M. purpureus than the unfermented. Amino acids L-methionine, L-serine, L-glutamic acid, L-valine glycine, L-leucine, L proline, L-threonine, L-histidine, and L-Sistine were higher (p < 0.05) in M. purpureus-fermented used rice than in C. crassa-fermented and the unfermented used rice. However, amino acids L-isoleucine, L- alanine, L-lysine, and L-tryptophan were higher (p < 0.05) in the used rice fermented with both C. crassa and M. purpureus, compared with the unfermented. L-tyrosine content was higher (p < 0.05) in M. purpureus-fermented used rice than in the unfermented. Furthermore, the antioxidant activities of the fermented products were higher (p < 0.05) than that of the unfermented. In addition, the antimicrobial activities of the fermented products against Staphylococcus aureus were higher (p < 0.05) than that of the unfermented used rice. Conclusion: In conclusion, the used rice fermented using C. crassa and M. purpureus improved the nutritional quality, as well as the antioxidant and antimicrobial activities of the products. J. Adv. Vet. Anim. Res., 6(2): 168-173, June 2019